1977
DOI: 10.1126/science.406671
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Immunization of Experimental Monkeys Against a Human Malaria Parasite, Plasmodium falciparum

Abstract: This is the first report of successful immunization of experimental monkeys against a human malaria parasite, Plasmodium falciparum. Of the five owl monkeys (Aotus trivirgatus) used in this pilot study, two served as controls and the other three were immunized with P. falciparum antigen consisting primarily of mature segmenters containing fully developed merozoites. Two injections of antigen emulsified with Freund's complete adjuvant were administered intramuscularly 3 weeks apart. Three weeks after the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…The results are similar to those obtained using whole merozoites and/or schizonts as immunogens (11,12,13,14). The protective effect induced by immunization with the 41-kD polypeptide is probably not dependent on strain specific determinant, on the basis of several observations.…”
Section: Discussionsupporting
confidence: 74%
“…The results are similar to those obtained using whole merozoites and/or schizonts as immunogens (11,12,13,14). The protective effect induced by immunization with the 41-kD polypeptide is probably not dependent on strain specific determinant, on the basis of several observations.…”
Section: Discussionsupporting
confidence: 74%
“…With P. falciparum, Voller and Richards observed a significant delay in the prepatent period following immunization of Aotus monkeys with formalin-treated schizonts of P. falciparum in adjuvant, but the induced immunity was not sufficient to protect the monkeys against death (312). Partial protection against homologous as well as heterologous P. falciparum challenge was induced in Aotus monkeys by immunization with P. falciparum merozoites in adjuvant (279,280). Immunization with mature schizont stages of P. falciparum conferred strong protection against homologous challenge in Saimiri monkeys (106), and Saimiri monkeys develop significant, long-lasting protection (up to 7 months) against challenge with homologous as well as (61,248), against P. lophurae in ducks and chickens (253), and against P. yoelii nigeriensis in mice (314).…”
Section: Empirical Observations Of Asexual Erythrocytic-stage Immunitymentioning
confidence: 99%
“…The ability of some species of new world monkeys to support the erythrocytic stage of malarial infection has allowed vaccination studies to be undertaken in these primates and early experiments showed that vaccination with merozoites or schizonts from Plasmodium falciparum protected against a lethal bloodstage infection (Mitchell et al 1977;Siddiqui, 1977). Many merozoite and schizont antigens have since been identified and their genes cloned and sequenced.…”
Section: Introductionmentioning
confidence: 99%